Clinical spectrum of osteopetrosis with secondary osteomyelitis of the mandible: Report of two cases - Sadaksharam Jayachandran; Manoharan Preethi (Wolters Kluwer Medknow Publications, 2018)
Osteopetrosis is an inherited disorder of the bone caused by mutations in gene that encode for carbonic anhydrase. This results in defective osteoclast function leading to resorption defects and formation of bones that are extremely dense and prone to fractures. In addition, it causes a variety of clinical manifestations in endocrine, nervous, orthopedic, hematologic, nephrologic, and dental. Among dental manifestations, osteomyelitis is the most serious complication caused by compromised blood supply resulting from encroachment of the medullary spaces by cortical bone. There are three subtypes of the disease-an autosomal dominant form also known as Albers-Schonberg disease or ADO II, malignant recessive infantile form, and an intermediate form. The ADO II can have an extremely varied clinical presentation ranging from an accidental finding from routine radiographic examination to poor prognosis. Here, we present two cases of ADO II with varied clinical, radiographic, and biochemical manifestations and discuss their management and dental implications.